A longitudinal investigation of perceived weight status as a mediator of sexual orientation disparities in maladaptive eating behaviors. (April 2019) - Luk, Jeremy W.; Miller, Jacob M.; Lipsky, Leah M.; Gilman, Stephen E.; Haynie, Denise L.; Simons-Morton, Bruce G.
Abstract: Sexual minority adolescents are more likely than heterosexual peers to engage in maladaptive eating behaviors such as restrictive dieting. However, prior studies relied on cross-sectional data and did not test potential mechanisms. This study examined longitudinal associations between adolescent sexual minority status and three maladaptive eating behaviors (restrictive dieting, diet pill use, and drug-related dieting) in young adulthood and tested higher perceived weight status as a mediator of observed disparities. Data were drawn from Waves 2 (11th grade in 2010/2011) to 7 (4 years post high school in 2015/2016) of the NEXT Generation Health Study, a U.S. national longitudinal cohort of adolescents ( n = 1925). Logistic regression analyses revealed that, relative to heterosexual females, sexual minority females were more likely to report any restrictive dieting (extreme food intake restriction) in the past year (62.9% vs. 37.0%; Adjusted Odds Ratio = 2.26, 95% CI = 1.07, 4.76). Associations between sexual minority status and diet pills use or drug-related dieting were not found. Results from structural equation modeling indicated that higher perceived weight status was a significant mediator of the association between sexual minority status and restrictive dieting among females. These findings highlight higher perceived weight status as an important cognitive mechanism explaining why sexual minority females are at heightened risk for restrictive dieting in young adulthood. To optimally inform prevention efforts, additional research is needed to test the extent to which minority stressors may shape weight perceptions and their contribution to maladaptive and disordered eating behaviors among sexual minority adolescents. Highlights: Sexual minority females were more likely to report past year restrictive dieting than heterosexual females. Direct associations between sexual minority status and diet pills use or drug-related dieting were not found. Perceived weight status was a mediator of the association between sexual orientation and restrictive dieting among females. Perceived weight status is an important cognitive mechanism explaining why sexual minority females are at heightened risk. Interventions may target factors that shape weight perception among sexual minority females.